功能矫治对安氏Ⅱ类错 [Image: see text] 畸形患者髁突位置影响的Meta分析 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2016)
OBJECTIVE: This study aimed to analyze the condylar position changes produced by functional appliances in class Ⅱ malocclusion by systematic review. METHODS: Electronic search was conducted using Chinese Biomedical Literature Database, China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals, Medline, Embase, Pubmed, and Cochrane Central Register of Controlled Trials. Studies on condylar position changes produced by functional appliances in class Ⅱ malocclusion were included. Risk of bias assessment and data extraction of included studies were conducted by two reviewers independently. The meta-analysis was carried out using Revman 5.1. RESULTS: Six studies were included (five high quality and one low quality). The condylar position showed no changes after Herbst treatment. The condylar posterior space after Twin-block treatment averagely increased by 0.31 mm (P<0.000 01), whereas the condylar anterior space averagely reduced by 0.32 mm (P<0.000 01). CONCLUSION: Twin-block appliance enables forward movement of the condylar position. This result contributes to the correction of class Ⅱ malocclusion.